Encouraging Community Reading Interest through Digital Libraries in Karawang Regency - Ine Nirmala; Nurul Ilmi; Fahrullah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Data from UNESCO shows that Indonesian people's interest in reading is only 0.001%, meaning that out of 1,000 Indonesians, only 1 person is an avid reader. This study aims to optimize the use of digital libraries, namely by making the community literate in technology and experiencing the various benefits of using digital libraries so that they can encourage people's interest in reading in Karawang Regency. We collect data by going directly to the community because we are literacy activists. The results of a survey in the community in Karawang Regency, from the age range of adolescents to adults, show that they have never visited the Regional Library of Karawang Regency. This implies that the interest in visiting the regional libraries to read books there is still low. This study aims to find out to what extent digital libraries can encourage people's interest in reading. In this digital age, people are more interested in holding gadgets than books. Recommendations for the Karawang Regional Library to be more aggressive in socializing digital libraries so that people can more easily access digital library services from their gadgets anytime and anywhere.